Hubungan Pola Makan Dan Aktivitas Fisik Dengan Status Gizi Anak Jalanan Kota Surabaya - Susanty, Ade Susanty; Solichan, Wachidatul Akhmalia; Mukarromah, Nur (Jurnal Keperawatan Muhammadiyah, 2019)
Lack of nutrition is the one of health problems that occurs in street children because of their irregular eating patterns and activities are not balanced with their food intake. In addition, with the most dominant activities of street children are singing, then selling and begging with uncertained work hours, street children are often also found until late night following city life. The research method is observational analytic using sectional design. The sample consists of 102 Street children of Surabaya. Sampling technique using Simple Random Sampling. The research instrument used Eating Pattern questionnaire and Physical Activity with validity 0.444 and reability 0.823, weight measurement with scales and height scale with microtoise. Data analysis was done by using spearman rank (rho) with significant level Î± <0.05. The results of the study, there is a relationship between eating pattern and physical activity with nutrition status of Surabaya street children. Proved by the results of statistical analysis of eating pattern with nitrition status of street children p = 0.000 <Î± = 0.05 and physical activity with nutrition status of street children p = 0.000 <Î± = 0.05. The conclusion of nutrition less can be related with eating pattern and physical activity of street children. So, it is necessary to pay attention towards their nutrition intake which received by Street children by giving them food 4 healthy 5 perfect and take a rest or sleep 9 until 11 hours per day to stabilized metabolism rate within their body of street children ofÂ  Surabaya.Â